Analysis of Clean Water Quality and Distribution in the Salate Area (RT 13/RW 03) of Passo Village, Baguala District, Ambon City - Pooroe, Sitri Marlina; Salakory, Melianus; Riry, Roberth Berthy (Jurnal Pendidikan Geografi Unpatti, 2024)
This study aims to analyze the quality of clean water and the distribution of clean water in the Shooting Range Complex (SalatE) RT 13 RW 03 Negeri Passo, Baguala District, Ambon City. This research uses a qualitative descriptive approach with a data collection period from August 21 to September 21, 2023. The method of taking physical samples was carried out on three water units representing water sources in the complex: distribution pipes from springs dug wells, and borehole water. Meanwhile, social aspect samples were taken from community members who own dug wells, bore wells, and those who use village government-owned water. In this study, samples were selected representatively from the population, namely 23 households (KK) out of 175 KK in the complex. The samples comprised 2 KK owners of dug wells, 8 KK owners of bore wells, and 12 KK users of village government-owned water. Data were obtained through observation, interviews, documents, and questionnaires. Data analysis was conducted based on the results of Laboratory Analysis. The results showed that the availability of clean water has yet to meet the needs optimally, both in terms of quality and quantity. In terms of quality, there is an indication that spring water in Desa Passo approaches the maximum requirements for clean water according to health regulations, especially in the Total Coliform parameter. It indicates the need for more attention to monitoring and managing water quality and improving infrastructure to ensure a safe and adequate supply of clean water for the people of Desa Passo.